A Review on the Contemporary Research on Radio Frequency Energy Harvesting - Sangaran Diagarajan, Manee; Ramasamy, Agileswari; Bt. Md Din, Norashidah; Naidu Vummadisetty, Praveen (International Journal of Engineering and Technology, 2018)
Radio Frequency harvesting has recently become one of the alternate approaches to power up low power wireless networks. This evolving technology opens the gate for positive energy renewal for wireless components. This paper presents a comprehensive review which includes all the important components in a RF energy harvesting system which are microstrip patch antennas, rectifier modules and power management modules. Different types of microstrip patch antennas and its designs and outputs are discussed. Rectifier modules with Schottky diodes operating under two different frequency bands are also compared and discussed. In addition, different methods of available power management circuits with different methods are also deliberated in this paper. This review also explores various key design issues and envisions some open research directions.Â Â